Memory effects and sustainable harvesting in a fractional-order predator-prey model with prey refuge and nonlinear harvesting - Rahman, Hiwa Hussein; Faraj, Bawar Mohammed (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study investigates the dynamics of a predator-prey model with fractional-order derivatives, incorporating factors such as prey refuge, nonlinear harvesting, and memory-dependent processes. The model is governed by a coupled system of Caputo fractional differential equations, where prey growth follows logistic dynamics with refuge parameter , and harvesting adopts a generalized nonlinear form. The predator’s functional response follows a Holling type II mechanism modified by prey refuge. We analyze existence, uniqueness, and stability of equilibrium points, along with the influence of fractional-order derivative on long-term behavior. Numerical simulations reveal that memory effects significantly alter system dynamics, leading to sustained oscillations, enhanced stability, or complex bifurcation patterns compared to classical integer-order models. Furthermore, we explore sustainable harvesting strategies by examining the impact of refuge and harvesting efforts on population persistence. Our findings highlight ecological implications of fractional-order dynamics in predator-prey systems, providing insights into biodiversity conservation and resource management.